ANALISIS PENGARUH KECEPATAN KENDARAAN BERAT TERHADAP DERAJAT KEJENUHAN PADA SEGMEN TANJAKAN SIMPANG EMPAT TAK BERSINYAL PAOK MOTONG - sahrudin sahrudin (PT LIB Research Cendekia, 2026)
This study examines the impact of heavy vehicle speed on traffics aturation levels and level of service at the uphill segment of theu nsignalized four-leg intersection in Paok Motong. Regressiona nalysis reveals a coefficient of determination (R²) of 0.6597,i ndicating that 65.97% of the variation in saturation level is explainedby heavy vehicle speed, while the remaining 34.03% is influenced byr oad geometry, vehicle type, environmental conditions, and othere xternal factors. The saturation degree (DS) of 1.12 places the segmenti n Level of Service F, characterized by forced flow, low speeds, andt raffic volumes exceeding road capacity. During normal hours, thea verage speed of heavy vehicles is 38.90 km/h, whereas during peakh ours it drops to 25.22 km/h. This speed reduction contributes toi ncreased traffic volume and density, leading to higher saturation,congestion, delays, and elevated accident risk. These findings highlight the need for targeted capacity evaluation and traffic management strategies on uphill road segments frequently used by heavy vehicles.